Cartesian Doubt Encourages Critical Thinking in Education - Wesly Baan (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
Critical thinking is a fundamental competency in modern education, enabling students to filter information, evaluate arguments, and make logical decisions. René Descartes, through the method of doubt (Cartesian Doubt), offers a systematic approach to building solid knowledge. This article analyzes the relevance of Descartes' method of doubt to education through three steps: theoretical, reflective, and applied. The study found that the principle of